Evolutionary design of a flexible, seasonally migratory, avian phenotype: why trade gizzard mass against pectoral muscle mass?. Issue 1903 (22nd May 2019) - Mathot, Kimberley J.; Kok, Eva M. A.; Burant, Joseph B.; Dekinga, Anne; Manche, Petra; Saintonge, Darren; Piersma, Theunis
Abstract : Migratory birds undergo impressive body remodelling over the course of an annual cycle. Prior to long-distance flights, red knots ( Calidris canutus islandica ) reduce gizzard mass while increasing body mass and pectoral muscle mass. Although body mass and pectoral muscle mass are functionally linked via their joint effects on flight performance, gizzard and pectoral muscle mass are thought to be independently regulated. Current hypotheses for observed negative within-individual covariation between gizzard and pectoral muscle mass in free-living knots are based on a common factor (e.g. migration) simultaneously affecting both traits, and/or protein limitation forcing allocation decisions. We used diet manipulations to generate within-individual variation in gizzard mass and test for independence between gizzard and pectoral muscle mass within individuals outside the period of migration and under conditions of high protein availability. Contrary to our prediction, we observed a negative within-individual covariation between gizzard and pectoral muscle mass. We discuss this result as a potential outcome of an evolved mechanism underlying body remodelling associated with migration. Although our proposed mechanism requires empirical testing, this study echoes earlier calls for greater integration of studies of function and mechanism, and in particular, the need for more explicit consideration of the evolution of mechanisms underlying phenotypic design.